Midterm outcomes of surgical strategy for secondary aorto-enteric fistula - Shuhei Miura; Ayaka Arihara; Yutaka Iba; Tomohiro Nakajima; Junji Nakazawa; Tsuyoshi Shibata; Yu Iwashiro; Kei Mukawa; Nobuyoshi Kawaharada (Annals of Vascular Surgery - Brief Reports and Innovations)
Objectives: Our surgical strategy for secondary aorto-enteric fistula (sAEF) encompasses one-stage open repair consisting of in situ anatomical prosthetic graft replacement with omentopexy following fistula repair. This study aimed to evaluate the midterm outcomes of our comprehensive surgical strategies for sAEF in a single-center series. Methods: Between 2010 and 2022, 16 patients (14 male individuals; median age, 76.3 years) who underwent surgical repair of sAEF were reviewed. Nine and seven patients previously underwent open repair (OR-AEF) and endovascular repair (EVAR-AEF) for abdominal aortic aneurysm (AAA), respectively. Results: Among patients who underwent OR-AEF (56.3 %) and EVAR-AEF (43.7 %), there were no significant differences in all variables, except for age (74.2 ± 4.8 vs. 79.1 ± 4.6 years, p = 0.028), interval from primary operation for AAA (66.9 ± 16.3 vs. 12.0 ± 11.4 months, p = 0.043), and clinical presentation with melena (77.8 % vs. 28.6 %, p = 0.049). Thirteen (81.3 %) patients were repaired with in situ anatomical graft replacement, whereas three (18.7 %) patients were unintentionally repaired with extra-anatomical bypass grafting based on intraoperative findings. Fistula repair was performed with duodenectomy in 14 (87.6 %) patients, direct suture closure in 1 (6.2 %), and sigmoid colectomy in 1 (6.2 %). The in-hospital mortality rate was 25.0 %. The 1- and 5-year overall survival and AEF-related event-free survival rates were 72.7 % and 49.8 %, and 77.0 % and 67.4 %, respectively. Patients who underwent complete removal of the contaminated prosthesis required suprarenal aortic clamping more frequently (72.7 % vs. 0 %, p = 0.007) than those who underwent partial removal. However, most were discharged without further oral antibiotic treatment (72.7 % vs. 0 %, p = 0.007). Patients who underwent complete removal had higher 5-year AEF-related event-free survival rate than those who underwent partial removal (69.3 % vs. 25.0 %, p = 0.069). Conclusions: Midterm outcomes of our surgical strategy may be acceptable in patients with sAEF. AEF-related event-free survival is potentially affected by complete infected prosthesis removal.